Background, realities and challenges of the national programs for the Comprehensive Rural Reform - Figueroa-Torres, Yady Nohelia; Pérez-Bello, Sandra Milena; Villamarín-Monroy, Claudia Liliana; Rincón-Pérez, Alfonso (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The peace agreements between the Colombian Revolutionary Armed Forces –FARC– and the National Government in Havana include a point of great relevance for the rural sector: the Comprehensive Rural Reform. This reform contemplates not only the productive aspect but also the concept of territory and all the actors involved in it; additionally, it seeks to improve the living conditions of the rural population through a structural transformation that respects the communities and their identities, and that provides opportunities to promote Rural Development.This article seeks to analyze the third aspect of point one of the agreement, the national plans for the integral rural reform, whose main objective is to overcome poverty and close the rural-city gap. In order to achieve this, first, the situations of rural poverty and rural-city gap in Colombia were described, and second, the proposals of the comprehensive rural reform to overcome poverty and reduce these gaps were revised, with the aim of understanding the context in which this reform is proposed to be implemented.